RELATION OF THE LATE ACTIVATION ZONE WITH THE LEFT VENTRICLE MYOCARIDUM CHANGES IN CANDIDATES FOR RESYNCHRONIZING THERAPY - S. V. Zubarev; M. P. Chmelevsky; M. A. Budanova; A. V. Ryzhkov; M. A. Trukshina; V. K. Lebedeva; M. Yu. Sitnikova; D. S. Lebedev (Российский кардиологический журнал)
Aim. By non-invasive methods, to assess relations of the zone of late electrical activation with changes in the left ventricle (LV) myocardium structure in patients — candidates for cardiac resynchronizing therapy. Material and methods. Totally, 37 patients included, with III functional class of chronic heart failure (CHF). In all patients, there was complete His left bundle branch block (LBBB) with QRS width 205 (190; 215) ms. Non-invasive electrophysiological mapping (NEM) was done with the “Amycard01C EP LAB” (EP Solutions SA,Switzerland), and magnetic-resonance imaging (MRI). At the first step, multichannel electrocardiography (ECG) was done. At the second step, MRI was done (MAGNETOM Trio A Tim 3 T, Siemens AG,Germany) with intravenous contrast “Gadovist” load. Changes inLV myocardium structure (post-inflammatory fibrosis or scar tissue) were evaluated by segments, within the delayed MRI contrasting. At the third stage, individual models of ventricles were built up. Activation ofLV epicardium in LBBB was evaluated by NEM.Results. Most oftenly the zone of late activation by NEM was found in the basal region on the border of posterior and lateral LV segments — 17 patients (46%) and in basal lateral LV segment — 8 (21%). By MRI, only post inflammatory fibrosis was found in 21 patient, among them in 5 the area of fibrosis was located on LV epicardium and overlapped the zone of late activation by NEM. Among 12 patients with ischemic heart disease 2 had scar onLV epicardium overlapping with the late activation zone. No one of 4 patients with combination of post-inflammatory fibrosis and ischemic scar did not show overlap of structural changes on the epicardium with the late activation zone.Conclusion. Combination of NEM and MRI in pre-operational period of patients investigation make it to relate structural changes inLV myocardium with the zone of its late electrical activation.